2017
DOI: 10.1155/2017/3728752
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electroacupuncture on PKMzeta in the ACC in Regulating Anxiety-Like Behaviors in Rats Experiencing Chronic Inflammatory Pain

Abstract: Chronic inflammatory pain can induce emotional diseases. Electroacupuncture (EA) has effects on chronic pain and pain-related anxiety. Protein kinase Mzeta (PKMzeta) has been proposed to be essential for the maintenance of pain and may interact with GluR1 to maintain CNS plasticity in the anterior cingulate cortex (ACC). We hypothesized that the PKMzeta-GluR1 pathway in the ACC may be involved in anxiety-like behaviors of chronic inflammatory pain and that the mechanism of EA regulation of pain emotion may inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…29 Previous studies have demonstrated that EA treatment significantly suppresses CFA-induced anxiety-like behaviors as assessed by the openfield test and elevated zero maze. 26 Additionally, EA has been reported to attenuate the anxiety-like behavior induced by L5 spinal nerve ligation assessed by the elevated plus maze. 30 These and our data suggest that EA can regulate the affective disorders caused by inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Previous studies have demonstrated that EA treatment significantly suppresses CFA-induced anxiety-like behaviors as assessed by the openfield test and elevated zero maze. 26 Additionally, EA has been reported to attenuate the anxiety-like behavior induced by L5 spinal nerve ligation assessed by the elevated plus maze. 30 These and our data suggest that EA can regulate the affective disorders caused by inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our laboratory and others have reported that EA can significantly reduce the anxiety-like behaviors associated with chronic pain. 26 However, the mechanism for these effects is unclear. We speculate that the effect of EA on pain aversion might be associated with the amygdala, although this has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture (EA), whose efficacy has been widely recognized, is applied to treat different states of multiple acute and chronic pain diseases. Notably, it has been further validated that EA inhibited the affective dimension of pain on the basis of analgesia [37][38][39] Accordingly, proofs of the alleviation of pain and accompanied negative emotion performed by EA through the abovementioned brain areas bring us a new insight into the underlying mechanism [36,[40][41][42][43]. However, based on the limited number of studies, it remains to be adequately explored how EA promotes the relief of affective pain-related aspects by acting upon ACC, hypothalamus, and CeA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Shao et al found that strong manual acupuncture stimulation could reduce pain-induced anxiety and phosphorylation of extracellular signal-regulated kinase in the anterior cingulate cortex (ACC) 29. Du et al confirmed that electro-acupuncture could decrease pain-induced anxiety-like behaviours by suppressing protein kinase mzeta activity in the ACC 30. Meanwhile, it has been shown that there is a shared neurobiological mechanism for emotional disorders and migraine 31–33.…”
Section: Introductionmentioning
confidence: 99%